PERAN ETIKA ISLAM DALAM MENGAMBIL KEPUTUSAN BISNIS - Abdau, Faizal (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT, 2025)
This study aims to analyze the role of Islamic ethics in business decision making and the extent to which Islamic ethical values influence the results of decisions taken by business people. The approach used is qualitatif with a survey method of Muslim business people in various business sectors. Data were collected through questionnaires and analyzed using descriptive and inferential statistical techniques. The results showed that Islamic ethical principles such as honesty, justice, and responsibility have a significant influence on the process and outcome of business decision-making. Internal factors such as level of religiosity and understanding of Islamic teachings, as well as external factors such as corporate culture and market pressure also influence the application of Islamic ethics in business practices. This study concludes that the integration of Islamic ethics in business decision management not only improves integrity, but can also strengthen consumer confidence and business sustainability